Role of CX3CL1/CX3CR1 Signaling Axis Activity in Osteoporosis - Wojdasiewicz, Piotr; Turczyn, Pawel; Dobies-Krzesniak, Barbara; Frasunska, Justyna; Tarnacka, Beata (Mediators of Inflammation, 2019)
Osteoporosis is a civilization disease which is still challenging for contemporary medicine in terms of treatment and prophylaxis. It results from excessive activation of the osteoclastic cell line and immune cells like macrophages and lymphocytes. Cell-to-cell inflammatory information transfer occurs via factors including cytokines which form a complex network of cell humoral correlation, called cytokine network. Recently conducted studies revealed the participation of CX3CL1 chemokine in the pathogenesis of osteoporosis. CX3CL1 and its receptor CX3CR1 present unique properties among over 50 described chemokines. Apart from its chemotactic activity, CX3CL1 is the only chemokine which may function as an adhesion molecule which facilitates easier penetration of immune system cells through the vascular endothelium to the area of inflammation. The present study, based on world literature review, sums and describes convincing evidences of a significant role of the CX3CL1/CX3CR1 axis in processes leading to bone mineral density (BMD) reduction. The CX3CL1/CX3CR1 axis plays a principal role in osteoclast maturation and binding them with immune cells to the surface of the bone tissue. It promotes the development of inflammation and production of many inflammatory cytokines near the bone surface (i.e., TNF-α, IL-1β, and IL-6). High concentrations of CX3CL1 in serum are directly proportional to increased concentrations of bone turnover and inflammatory factors in human blood serum (TRACP-5b, NTx, IL-1β, and IL-6). Regarding the fact that acting against the CX3CL1/CX3CR1 axis is a potential target of immune treatment in osteoporosis, the number of available papers tackling the topic is certainly insufficient. Therefore, it seems justified to continue research which would precisely determine its role in the metabolism of the bone tissue as one of the most promising targets in osteoporosis therapy.